The Philosophical Construction of Legal Justice by John Rawls and Gustav Radbruch and Its Relevance in the Context of the Indonesian Legal System - Tohari, Ilham; Musoffa, Ahmad; Rosidah, Aminatur; Toriqirrama, Faby (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2026)
The purpose of this article is to explore the philosophical constructions of legal justice proposed by two prominent thinkers, John Rawls and Gustav Radbruch, and assess their relevance in the context of the Indonesian legal system. Employing a qualitative approach, an in-depth analysis is conducted on their original works, including Rawls' "A Theory of Justice" and Radbruch's "Statutory Lawlessness and Supra-Statutory Law." The data management process involves categorization to facilitate a comprehensive comparative analysis. The results of this article provide profound insights into key concepts in the legal justice philosophies of Rawls and Radbruch. The understanding gained will be used to evaluate the relevance of these theories in addressing the dynamics and complexity of the Indonesian legal system. From each concept of justice by Rawls and Radbruch, it is evident that there are several relevant concepts to be actualized in the context of the Indonesian legal system